Development of water quality index of ex-mining ponds in Malaysia / Isa Baba Koki - Isa Baba , Koki (2017)
Assessment of the water quality of ex-mining ponds for its proper utilization is pertinent considering the metal pollutants, and lack of proper environmental measures associated with the mining operations. Water samples from selected lakes in the Central Region of Peninsular Malaysia (Selangor and Negeri Sembilan) and Malacca from the Southern part were analysed in-situ for pH, DO, SS, EC, BOD, AN, and TDS; while metal elements including As, Cd, Pb, Mn, Fe, Na, Mg, and Ca were analysed off-site using inductively coupled plasma mass spectrometry and verified via certified reference materials. The variations in these water quality parameters were explored with chemometric techniques. The results from the principal component analysis, factor analysis and hierarchical cluster analysis suggested that in addition to the degree of contamination, the variations in heavy metal concentrations were mainly attributed to the ex-mining activities, whereas deviations in BOD, TDS, AN, and EC were subjected to the current domestic inputs. The linear discriminant analysis showed that water samples from the ex-mining ponds were highly associated with the concentrations of Mn, Cd, Ca and As; the model constructed with the training set gave a precise prediction with R2 = 1.000, with no misclassification shown with the validation set. In Klang Valley, ex-mining ponds generally show low pH compared to the other lakes; the As and Cd levels recorded in most of the ex-mining ponds surpassed the limits of the Malaysian Water Quality Standard which make them unfit for domestic uses. A study of man-made lakes in Melaka and Negeri Sembilan revealed basic pH and low metal concentrations (below the reference values) in which As, Mn, and Mg were associated with ex-mining ponds while pH and Na were associated with other lakes. In this case, the high positive loadings of pH, DO, Ca, and TDS on principal component 1 suggests the absence of significant anthropogenic input. Overall, the differences in geology and domestic inputs into the ex-mining ponds significantly affect the water quality and results in variation in the levels of metals and physical-chemical parameters. The associated health risk via ingestion and dermal contacts were also modelled using Monte Carlo simulation and the estimated carcinogenic and non-carcinogenic risks for both adult and children were compared with their benchmarks. Water quality index was then formulated based on the Malaysian Water Quality Standard and results from chemometric analyses were applied in the parameter selection so as to minimize subjectivity; consequently, As, Cd, Pb, pH, DO, BOD and AN were chosen. The index was applied for the evaluation of water quality of the above mentioned lakes where most of the ex-mining ponds in Klang Valley were classified as very polluted, while those in Melaka and Negeri Sembilan were rated as excellent.